2012
DOI: 10.1074/jbc.m111.325027
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oncogenic MicroRNA-203 Induces Senescence by Targeting E2F3 Protein in Human Melanoma Cells

Abstract: Background: MicroRNA-203 is down-regulated, and its exogenous expression inhibits cell growth in human melanoma cells. Results: MicroRNA-203 induced senescence by cell cycle arrest through targeting E2F3. Conclusion: MicroRNA-203 is a novel senescence-associated microRNA in melanoma cells. Significance: This study has revealed the relationship between senescence and carcinogenesis in melanoma cells with respect to dysregulation of anti-oncogenic microRNA-203.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 37 publications
7
68
1
Order By: Relevance
“…Our analysis confirmed the previous report of miR-193b downregulation in metastatic melanoma [49]. In addition, downregulation of miR-203, miR-200a, miR-200c, miR-205 was previously reported in several melanoma cell lines [50][51][52]. Our data reveal that the loss of expression in these miRNAs occurs predominantly in metastatic melanomas compared with primary.…”
Section: Mirna Profiling Of Primary and Metastatic Melanoma Tumorssupporting
confidence: 92%
“…Our analysis confirmed the previous report of miR-193b downregulation in metastatic melanoma [49]. In addition, downregulation of miR-203, miR-200a, miR-200c, miR-205 was previously reported in several melanoma cell lines [50][51][52]. Our data reveal that the loss of expression in these miRNAs occurs predominantly in metastatic melanomas compared with primary.…”
Section: Mirna Profiling Of Primary and Metastatic Melanoma Tumorssupporting
confidence: 92%
“…p63 was shown to be directly targeted by miR-203 in mouse skin epithelial cells (50). In several types of human cancer cells, ABCE1, Abl1, and E2F3 were shown to be directly targeted by miR-203 (33,35,36,68). In this study, we found that miR-203 also targets p63 in RMS cells (Fig.…”
Section: Mir-203 Exerts Tumor-suppressive Effects In Rms Cells-supporting
confidence: 56%
“…It can also target Hakai and inhibit the growth of human colon adenocarcinoma (28). Additionally, those genes involved in the regulation of cell proliferation, apoptosis, cell cycle progression, migration and invasion, are also the targets of miR-203, including Robo1, Kif5b, E2F3, LASP1, ASAP1, PKCα, BIRC5, Bmi-1 and DeltaNp63 (23)(24)(25)(26)(29)(30)(31)(32)(33). Whether these miR-203 targets are also involved in the development and progression of NB remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%